Pembelajaran Biologi Melalui Latihan Soal Pilihan Ganda untuk Siswa SMA - Gaung Perwira Yustika (Universitas Mathla'ul Anwar Banten, 2018)
BIOLOGY LEARNING BY DOING MULTIPLE CHOICE QUESTION FOR SENIOR HIGH SCHOOL STUDENTS. Multiple choice question learning and understanding can help learning process in the classroom. To maximize its use as learning tool, the students can have finish the task in 2 ways: first they will finish the Multiple-Choice Question (MCQ) task during the class hours and submit it when the class over. Or it can be homework to the students and hand it over at the next meeting session. The research showed that the instructor/teacher prefer on use multiple choice not only due to administration, time saving and simplicity but also objective and consistent. Furthermore, the student based on research result more like Multiple choice question assignments because they can eliminate wrong answers and these questions form more objective than anothers. Beside that with this method the student can participate actively in learning process.